Demurrage and detention: From operational challenges towards solutions - Katrien Storms; Christa Sys; Thierry Vanelslander; Ruben van Deuren (Journal of Shipping and Trade (JST), 2023)
Reduced free time and increased fees for demurrage and detention create organizational challenges with respect to intermodal transport. As a result, actors within the maritime supply chains are confronted with greater complexity and higher risk of costs; and, therefore, often fall back on transportation by truck to and from the hinterland. That is why the present research examines the impact of this evolution on the bottom line of the involved actors from a maritime supply chain perspective. The research approach consists of reviewing the relevant literature, analyzing the available sector data obtained through interviews and professional experience, and validating the proposed solutions. Starting from the research results, the problem-solving discussions resulted in the following top three as feasible solutions: digitalization, extra 'free time' for hinterland locations, and more attention during the negotiation process.
Keywords: 650; Container shipping; Demurrage; Detention; Free time; Intermodal transport; Maritime supply chain